A Theoretical Explanation of the Influence of Gentrification on Neighborhood Crime. Issue 1 (2nd January 2016) - Barton, Michael S.; Gruner, Colin P.
ABSTRACT: Gentrification and other types of neighborhood revitalization strategies have been promoted as viable crime reduction strategies, but empirical assessments of this relationship produced inconsistent results. The mixed results were partly due to a narrow theoretical focus on social disorganization and routine activities, but also because of a limited conceptualization of gentrification. The current study draws on gentrification literature more broadly and incorporates insights from additional criminological theories to provide a more complete understanding of how gentrification is related to neighborhood crime. Specifically, three pathways through which gentrification influences neighborhood crime are identified.